(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2008)
A laboratory based column leaching experiment was set up to study the retention of nitrate (NO3- ) and phosphate (PO43-) in three Bangladesh soils (Ghatail, Tejgaon and Sonatola) and their subsequent uptake by plants (Ipomoea aquatica). The investigation showed that the higher the clay contents, the higher was the retention of NO3- and PO43- by the soils and the lesser was their transfer into the growing plants. Again the higher the pH values in soils, the lower was the retention of NO3- and PO43- elements retained in the soils and the higher was the transfer of the elements into the growing plant. Retention of nitrate and phosphate followed the order: Ghatail>Tejgaon> Sonatola while the transfer to plant was in the order Sonatola>Tejgaon>Ghatail. Key Words: Nitrate, Phosphate, Retention, Leaching, Plant Uptake. DOI: 10.3329.bjsir.v43i1.858 Bangladesh J. Sci. Ind. Res. 43(1), 67-76, 2008